LEMAHNYA KEAMANAN BANK PEMERINTAH DI INDONESIA: STUDI KASUS PERETASAN BANK BRI TERHADAP NASABAHNYA - Jonathan Jordan Sianipar; Marta Solavide Naibaho (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2024)
A government bank is a bank that is partially or wholly owned by the Indonesian government. All profits of state-owned banks also belong to the government. The types of government banks include Bank Rakyat Indonesia (BRI), Bank Mandiri, Bank Negara Indonesia (BNI), Bank Tabungan Negara (BTN), and Bank Syariah Indonesia (BSI). In the past in the banking world, to conduct all forms of transactions must go through a bank teller, and now because of the changing times, then all forms of transactions can be accessed easily through m-banking, which we can access on our handphone, but behind the ease of accessing it, on the other hand, it also has negative impacts such as the ease with which our bank accounts can be hacked by others. For this reason, the purpose of this paper is to understand what factors cause weak bank security and how banks should handle hacking cases that occur to their customers, by using empirical juridical research methods, namely raising case studies about Bank BRI hacking that actually occur in society.